PENINGKATAN KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA SISWA KELAS X SMK NEGERI 1 TUNGKAL JAYA - Ayunani, Rina Putri; Wardarita, Ratu; Puspita, Yenny (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
This research aims to describe the improvement in the ability to write text reports on observations and learning activities of class X students at SMK Negeri 1 Tungkal Jaya through the application of the Problem Based Learning model. The method used is the classroom action research method (PTK). The data analysis technique used is the cumulative descriptive analysis technique. The form of action given uses the Problem Based Learning model. This research was carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The results of the writing test in cycle I showed that 17 students scored ≥70 (37%), while in student activities there were 22 students who were polite (56%). In cycle II there were 34 students who got ≥70 (87%), while in student activities there were 35 students who were polite (90%). This means that students' writing abilities increased by 50% in cycle II, and student activity increased by 34% in cycle II. Based on the research results and success criteria, it can be concluded that the ability to write report texts based on observations of class X students at SMK Negeri 1 Tungkal Jaya has increased.